The 360° beach video: a supporting mindfulness intervention with virtual reality - Naini, Rohmatus; Wibowo, Mungin Eddy; Purwanto, Edy; Mulawarman, Mulawarman; Anwas, E. Oos M. (International Journal of Informatics and Communication Technology (IJ-ICT), 2025)
This article describes optimizing virtual reality (VR) with a 360° beach video model used for mindfulness interventions. Using VR with 360° beach videos to support the presence of an immersive environment can effectively support mindfulness practices. Students are interested in the integration of technology in school counseling. VR helps in creating immersive environments such as forests, beaches, waterfalls, etc. so that students focus more on practicing mindfulness and attention in the current moment. This article focuses on optimizing 360° beach videos in the breathing mindfulness process so that it helps bring out real experiences. Obstacles to practicing mindfulness include lack of focus, mind wandering and not concentrating. through the use of 360° beach videos with VR can increase focus and be more effective in mindfulness practice.